Capturing growth indices on the road to health booklets in clinics in Free State, South Africa - Patience O. Legoale; Mashudu Manafe (AOSIS, 2024)
Background: Growth monitoring plays an essential role in the development of young children. Anthropometric indices are of utmost importance for healthcare professionals to identify children at risk of inadequate growth and malnutrition. Aim: This study aimed to assess the capturing of the growth indices in the Road to Health Booklets (RTHB) in clinics. Setting: The study was carried out in Mangaung Metropolitan municipal clinics in the Free State province, South Africa. Methods: A descriptive quantitative study was conducted using a checklist to audit 264 RTHBs. Descriptive statistics were used to analyse data. Results: The findings showed that birth weight was recorded in most 99% (n = 262) of the RTHBs. The mid-upper arm circumference (MUAC) was not recorded in 58% (n = 153) of the cases during the last visit. Weight-for-Age (WfA) was routinely plotted in 91% (n = 241) of the RTHB. The length or Height-for-Age (LHfA) was plotted in 38% (n = 99) of the RTHB and Weight-for-Length or height (WfLH) was plotted in 31% (n = 81) of the RTHB. Conclusion: The results demonstrated that certain anthropometric measures including MUAC, length, or height were absent from the records of the RTHB. Consequently, RTHB may not be effectively used as a means of evaluating nutritional status, affecting early detection of malnutrition in children. Contribution: The research makes a valuable addition to the existing body of knowledge for monitoring growth and measurement of anthropometric indices in the RTHB, as well as the appropriate execution of these practices.